The Matching Efficiency of Regional Labour Markets A Stochastic Production Frontier Estimation, France 1990-1995 - Aomar Ibourk; Bénédicte Maillard; Sergio Perelman; Henri R. Sneessens (Institute for the Study of Labor (IZA), 2001)
We evaluate the determinants of matching efficiency changes through a stochastic Cobb- Douglas production frontier model extended to allow the efficiency coefficient to depend on variables meant to capture workers and firms characteristics. We apply this methodology to examine regional disparities in France over the period 1990-1995. About 30% of the efficiency changes observed over time and some 25% of the cross regional differences can be explained in terms of changes in firms and workers characteristics. Regional differences in matching efficiency are fairly stable over time and negatively correlated to the regional unemployment rates.
Keywords: J64; C24; 330; Matching efficiency; regional unemployment; stochastic frontier; Regionaler Arbeitsmarkt; Matching; Regionale Arbeitslosigkeit; Regionale Disparität; Technische Effizienz; Cobb-Douglas-Produktionsfunktion; Stochastischer Prozess; Schätzung; Frankreich